EVALUATION OF LEVEL OF INDIVIDUALS WITH PHYSICAL DISABILITY AFTER-EFFECTS OF LEPROSY WHICH LIE IN ATTENDANCE IN PHYSICAL REHABILITATION CENTER (Fiep Bulletin - online, 2013)
Introduction: Estimates suggest that approximately 20% of patients treated for leprosy or Hansen's disease may present physical disabilities and psychosocial restrictions, they often need some kind of intervention with rehabilitation and / or continuity of care. In Brazil, approximately 23% of leprosy patients have some type of physical disability after discharge. Objective: The aim of this study was to evaluate the degree of disability of individuals with leprosy sequelae that are in physical rehabilitation. Methodology: This is a cross-sectional study with 20 individuals diagnosed with leprosy who are in rehabilitation physiotherapy clinic in UNIOESTE. Sensory evaluation was performed and followed by sensitive tests of muscle strength, inspection and palpation of peripheral nerve trunks of upper and lower limbs, and face assessment according to the criteria of the Ministry of Health Results: In this study, individuals with sequels leprosy had mostly physical disability 1, followed by physical disability 2. The percentage presented with grade 1 (75%) and grade 2 (25%). There were no patients with grade 0 of disability research. Conclusion: According to our sample, most individuals with leprosy sequelae have grade 1 disability.
Keywords: Leprosy; Physical Disability; Rehabilitation